The Full Day School Program and Its Contribution to Student Learning Outcomes: Experience from English Subject (Indonesian Journal of Curriculum and Educational Technology Studies, 2021)
The implementation of a full-day school program at MTs. Negeri 2 Brebes has successfully achieved the goal of learning. Research methods are qualitative approaches. The research design uses a case study. The research focuses on the full-day school program's contribution to student learning outcomes of English subject with the object’s alumni of full-day school classes, English teachers, and deputy head of curriculum at MTs. Negeri 2 Brebes. Data collection technique’s semi-structured interviews, unstructured interviews, and literature reviews. Data validity techniques use source triangulation techniques. Data analysis techniques use Miles and Huberman analysis. The study results are: First, the learning objectives of full-day school program implementation at MTs. Negeri 2 Brebes have been achieved. Second, implementations of full-day school programs at MTs. Negeri 2 Brebes can contribute to improving English learning outcomes. Third, the obstacle is the gap in students' grades between full-day school and regular. Abstrak Implementasi program full day school di MTs. Negeri 2 Brebes telah berhasil mencapai tujuan pembelajaran. Metode penelitian pendekatan kualitatif. Jenis penelitian studi kasus. Fokus penelitian kontribusi program full day school terhadap hasil belajar siswa mata pelajaran Bahasa Inggris dengan objek alumni kelas full day school, guru Bahasa Inggris, dan wakasek bagian kurikulum di MTs. Negeri 2 Brebes. Teknik pengumpulan data wawancara semi terstruktur, wawancara tak terstruktur, dan tinjauan literatur. Teknik keabsahan data menggunakan teknik triangulasi sumber. Teknik analisis data adalah analisis Miles dan Huberman. Hasil penelitian. Pertama, tujuan pembelajaran implementasi program full day school di MTs. Negeri 2 Brebes telah tercapai. Kedua implementasi program full day school di MTs. Negeri 2 Brebes dapat memberikan kontribusi yang mempengaruhi peningkatan hasil belajar Bahasa Inggris. Ketiga salah satu kendalanya adalah adanya kesenjangan nilai antara siswa kelas full day school dengan siswa kelas reguler.